Association Between Physical Exercise and Mental Health During the COVID-19 Outbreak in China: A Nationwide Cross-Sectional Study - Nie, Yingjun; Ma, Yuanyan; Wu, Yankong; Li, Jiahui; Liu, Ting; Zhang, Ce; Lv, Chennan; Zhu, Jie (Frontiers in Psychiatry, 2021)
The COVID-19 has undergone several mutations, and caused deleterious effects on physical and mental health. Physical exercise has a positive effect on enhancing immunity and reducing the negative consequences of unhealthy emotional states caused by COVID-19. However, there is a severe lack of psychological exercise intervention measures in most countries, and individuals in social isolation have no access to mental healthcare during the pandemic. This study surveyed the association between physical exercise and mental health burden during the COVID-19 outbreak in China and to better understand the influence of different physical exercise types on reducing mental health burden during the pandemic. Analysis of variance, the chi-square test and Spearman’s correlation analysis were used for statistical analysis. 14,715 participants were included. The results showed that Chinese residents had several poor mental health conditions during the COVID-19 outbreak. And there was a significant positive correlation between the extent of adverse effects on mental health and provincial proportions of confirmed COVID-19 cases (r=0.365, P＜0.05).Some main factors caused an unhealthy psychological status, including epidemic severity (62.77%, 95% CI 58.62%-65.64%), prolonged home quarantine (60.84%, 95% CI 58.15%-63.25%), spread of large amounts of negative information about COVID-19 in the media (50.78%, 95% CI 47.46%-53.15%), limitations in daily life and social interaction (45.93%, 95%CI 42.46%-47.55%), concerns about students' learning (43.13%, 95% CI40.26%-45.48%) and worries about being infected (41.13%, 95% CI 39.16%-45.23%). There was a significant association between physical exercise and mental health. The largest associations were seen for home-based group entertainment exercise (i.e., family games, badminton, ball games), Chinese traditional sports (i.e., Chinese martial arts, Taijiquan and Qigong), and popular sports (i.e., yoga, video dancing, sensory-motor games and whole-body vibration), as well as durations of 30 min to 60 min per session, frequencies of three to five times per week and a total of 120 min to 270 min of moderate-intensity exercise weekly during the COVID-19 outbreak (p<0.05).